Temperature-Programmed Reduction of Copper-Manganese Catalysts Derived from Biomass Activated Carbon - Arfaezah, Anuar; Ibrahim, Yakub; Norsuzailina, Mohamed Sutan; Cirilo, Nolasco-Hipolito; Yun Hin, Taufiq-Yap (JASPE, 2014)
This study investigates the potential of bimetal impregnated catalysts supported on activated carbon derived from biomass for Selective Catalytic Reduction (SCR) of Nitrogen Oxides (NOx) with ammonia (NH3). The bimetal catalysts, Copper-Manganese (Cu-Mn) was deposited onto palm kernel shell (PKS) and coconut shell (CS) via impregnation method and calcined at 250 °C. Hydrogen Temperature-programmed reduction analysis (H2-TPR) using 5% Hydrogen gas (H2) in Argon (Ar) have been carried out to study the effect of different variables such as metal impregnation and support properties on the reduced states of the catalysts. Besides, FTIR, TGA and XRD were also used to characterize the catalysts. It was observed that impregnation of bimetals enhanced the catalyst characteristics where include important results from FTIR, TGA, XRD and H2-TPR. Based on the results presented in H2-TPR analysis, it was observed that the reduction peak of bimetal catalysts deposited on palm kernel shell activated carbon shifted to high temperature, about 597 °C. This demonstrates the intensity of the precursor interaction exists and a higher dispersion of bimetals on the surface of the support. In addition, the higher dispersion of bimetals was shown in XRD analysis. Hence, palm kernel shell-derived catalysts could be new and promising catalysts in SCR system.